1999
DOI: 10.1259/bjr.72.858.10560346
|View full text |Cite
|
Sign up to set email alerts
|

Perianal Paget's disease.

Abstract: Perianal Paget's disease is rare. Unlike Paget's disease of the nipple, which is always associated with a subjacent breast adenocarcinoma, perianal Paget's disease is not always associated with a subjacent or visceral malignancy. The treatment recommendation in nearly all reported cases has been surgical excision. Radiation therapy is seldom used as a curative treatment. A case of perianal Paget's disease is described in whom radiation therapy was used with a curative intent after four unsuccessful surgical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 9 publications
0
29
0
3
Order By: Relevance
“…Darier and Coulillaud [5], in 1893, described the first patient with EMPD involving the perianal area. Perianal EMPD accounts for less than 1% of anal disease and affects more commonly female, with a peak of incidence of 60 year old [6]. Several difficulties are combined to make a clinical diagnosis of this condition [7].…”
Section: Discussionmentioning
confidence: 99%
“…Darier and Coulillaud [5], in 1893, described the first patient with EMPD involving the perianal area. Perianal EMPD accounts for less than 1% of anal disease and affects more commonly female, with a peak of incidence of 60 year old [6]. Several difficulties are combined to make a clinical diagnosis of this condition [7].…”
Section: Discussionmentioning
confidence: 99%
“…This data was collected by searching English-language journals included in the PubMed database and published between 1991 and 2012, using the keywords ‘EMPD' and ‘radiotherapy'. 15 available articles were identified [15,16,17,18,19,20,21,22,24,25,26,27,28,29,30]; however, 1 article [30] was excluded from this analysis because the applied radiotherapy methods were not described in detail. Therefore, 66 patients (21 male, 45 female; median age 73 years (range 38-92 years)) from 14 articles were analyzed (table 3).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, surgical margin status did not predict disease recurrence. Radiotherapy appears to effectively reduce local recurrence among patients with uncertain surgical margins or medically inoperable EMPD [15,16,17,18,19,20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…Perianal Paget disease occurs more commonly in women and usually begins in or after the 5th decade 5 . In contrast to Paget disease of the nipple, which is commonly associated with an underlying ductal carcinoma, ppd is associated with subjacent or visceral primary malignancies (mainly of the rectum, cervix, or urethra) in only 20% of patients who present with the condition, and yet histologically, the two diseases are identical 1 .…”
Section: Case Descriptionmentioning
confidence: 99%
“…However, more detailed cases of successful treatment with radiotherapy have recently been published 4,5,[11][12][13][14][15][16][17][18] . Several investigators have made a strong case for the use of primary radiotherapy for curative intent in patients not considered suitable for surgery, and for the use of postoperative radiotherapy after resection 4,5,11 . Besa et al 11 observed a 36%-66% rate of positive margins after surgical excision alone in their series of 65 patients with empd of the perineal skin, and the actuarial local recurrence rate for patients treated with surgery was 40% within 5 years.…”
Section: Case Descriptionmentioning
confidence: 99%